Case study of the emergency exits of the Institute of Science, Engineering and Technology of UFVJM (International Journal of Geoscience, Engineering and Technology, 2021)
In the field of civil construction, one of the areas that has shown potential growth concerns investments in Fire Safety, in view of the countless losses that have already been accounted for in occurrences of accidents that culminated not only in material losses, but also in lives human. This shows the importance of applying techniques and equipment that prevent the spread of fire in buildings and ensure the physical integrity of users, as well as the conservation of heritage. The objective of this work is the analysis of the Emergency Exits in the building of the Institute of Science, Engineering and Technology (ICET) of the Federal University of Vales do Jequitinhonha e Mucuri (UFVJM), according to what is prescribed in the Technical Instructions of the Minas Gerais Military Firefighters (CBMMG), aiming at security in this educational environment. From the analysis carried out at the site, it was found that about 92% of the elements of emergency exits had some irregularity when compared to the requirements determined by Technical Instruction 08 - Emergency Exits in Buildings (IT - 08) of CBMMG. Regarding the analyzed widths, approximately 58% complied with the minimum width of 1.10m that IT 08 indicates. In this way, it is recommended that the emergency exits be adapted, especially in accesses where the width has been reduced due to the presence of obstacles.
Keywords: Emergency Exits; Safety Measures; Technical Instructions; Fire Safety